Association of education level with the risk of female breast cancer: a prospective cohort study - Runxue Jiang; Xia Wang; Zhiguo Sun; Shouling Wu; Shuohua Chen; Haifeng Cai (BMC, 2023)
Abstract Background Breast cancer is a serious threat to female health, and its incidence varies with education level (EL). In the present study, the association between EL and the risk of developing female breast cancer was investigated. Methods From May 2006 to December 2007, 20,400 observation subjects in Kailuan Cohort received questionnaires and were subjected to clinical examinations for data collection on baseline population characteristics, height, weight, lifestyle and past disease history. Then, these participants were followed up with from the date of recruitment to December 31, 2019. Cox proportional risk regression models were used to analyse the association between EL and the risk of developing female breast cancer. Results The cumulative follow-up period of 20,129 observation subjects that meet the inclusion criteria of this study was 254,386.72 person-years, and the median follow-up time was 12.96 years. During the follow-up period, 279 cases of breast cancer were diagnosed. In comparison with the low EL group, the risk of developing breast cancer was significantly higher in the medium (hazard ratio [HR] (95% confidence interval [CI]) = 2.23 (1.12-4.64)] and high [HRs (95% CI) = 2.52 (1.12-5.70)] EL group. Conclusion An increased risk of breast cancer was associated with a higher EL, and some certain factors, such as alcohol use and hormone therapy, may play a mediating role.